The Effect of Group Cognitive-Behavioral Therapy on the Lifestyle of Patients With Hepatitis B - Marjan Faramarzi; Javad Khalatbari; Shohreh Ghorban Shiroudi; Khadijeh Abolmaali (Iran University of Medical Sciences, 2022)
Background: To promote general health in patients with hepatitis, it is vital to develop effective interventions to improve the lifestyle of these patients. The present study aimed to investigate the effectiveness of group cognitive-behavioral therapy (CBT) on the lifestyle of patients with hepatitis B. Methods: This was a quasi-experimental study with pretest-posttest control group design. A sample of patients with chronic hepatitis B was selected from all patients visiting specialized clinics in Tehran -Iran in 2021. Thirty patients with hepatitis B were selected and randomly allocated to two experimental and control groups (15 patients per group). Eight sessions of group CBT (one 90-minute session per week for two months) were performed, and the post-test was then administered to both groups. The data was collected by the Health Promoting Lifestyle Profile-II (HPLP-II) and analyzed via the analysis of covariance (ANCOVA) and t-test in SPSS 26.  Results: There was no significant difference between the lifestyle mean score of the groups in the pre-test stage. The mean post-test score of the experimental and control groups were 133.42±6.28 and 94.76±5.68 respectively (P<0.001). The group CBT increased health promoting lifestyle indicators, including health responsibility (P=0.029), physical activity (P=0.050), nutrition (P=0.045), spiritual growth (P=0.045), interpersonal relations (P=0.002), and stress management (P=0.001) in the patients with hepatitis B. Conclusion: The findings indicated the effectiveness of group CBT in improving the health-promoting lifestyle of patients with hepatitis B. CBT can thus be used by clinical psychologists and psychiatric nurses to promote a healthy lifestyle in these patients.